Virtual Private Network Server and Adblock Server using Raspberry Pi with Parental Control - Md Yusoff, Siti Intan Nasuha; Baharudin, Shahidatul Arfah (Journal of Computing Technologies and Creative Content, 2020)
Technology becomes useful to people, but apart from being useful. It also can become a threat. Virtual Private Network (VPN) is one of the ways to secure and prevent the attack in wireless technology. It is a secure connection so that hackers will not be able to sniff the packet from their victims. This project focused on developing an integrated server using Raspberry Pi to host a VPN server, advertisement blocking server, and parental control and to test the security of virtual private network connection and the functionality of advertisement blocking and parental control. On this project, the admin can control and monitor their VPN server by itself without worry the data security because only the admin can see the data. Besides that, this project will have an advertisement blocking server. Users can access the internet without advertisement. Lastly, parents can block all the websites and pages to control and monitor their children’s activities during access to the internet.